Customizable network update planning in SDN. (1st September 2019) - Luo, Shouxi; Yu, Hongfang; Luo, Long; Li, Lemin
Abstract: Updating network configurations responding to dynamic changes is a error-prone task in SDN. During the update process, in-flight packets might misuse different versions of rules, and "hot" links could be overloaded due to the unplanned update order. As for the problem of misusing rules, recently proposed suggestions like two-phase mechanism and Customizable Consistency Generator (CCG) have provided generic and customizable solutions. Yet, there does not exist an approach that is flexible to avoid the transient congestion on hot links respecting to diverse user requirements like guaranteeing update deadline, managing transient throughput loss, etc.; controllers are in urgent need of such a solution. In this paper, we propose CUP, Customizable Update Planner, to seek the solution. Different from prior approaches that adopt fixed designs for a single purpose like optimizing the update speed (e.g., Dionysus) or avoiding congestions (e.g., zUpdate, SWAN), CUP introduces generic linear programming models to formulate user-specified requirements and the corresponding update planning problem. By solving these customized models, CUP is able to plan network updates according to a large fraction of user requirements, such as guaranteeing deadlines, prioritizing operation orders, managing throughput loss, etc., while avoiding transient congestion. We prototype CUP on Ryu and employ it to arrange updates for networks built upon Mininet. Results confirm the flexibility of CUP while indicating that it always obtains the "best" update plans following the user's wish.